Corporate carbon strategies, carbon accounting and performances of ISO14001-certified companies in Malaysia - Kasbun, Nur Fatin (2020)
The concern over environmental protection and corporate sustainability issues has increased in recent years, especially when carbon dioxide (CO2) emission has been scientifically proven as the ultimate reason for climate change. Likewise, the accounting role has evolved over time emphasizing different growth of information including carbon accounting utilization. However, despite the growth of interest to achieve sustainability by mitigating CO2 emissions, businesses are still uncertain about the kind of carbon strategies and tools that could enhance firm performances particularly corporate carbon performance. Companies are reluctant due to the perception that the sustainability effort is too complex to comply. On top of that, in Malaysia, the poor record of companies‘ participation in carbon emissions mitigation programs; and the world climate pledge that Malaysia ratified is far from being achieved. Based on these critical reasons, carbon emissions mitigation is a critical effort as carbon emissions affect business activities and behavior. This study examined the carbon dioxide traits that incorporated into organizations‘ corporate strategy which later emerged as one of the corporate strategies. The study also determined the importance of carbon accounting in capturing carbon information and consequently enhanced the organizations‘ carbon and financial performances. Due to scarce empirical studies in this perspective, this study examined the direct and indirect effects of the constructs, which comprise of corporate carbon strategies, carbon performance, carbon accounting‘s mediating role, and government‘s carbon initiatives moderating role. This study integrates resource-based theory, legitimacy theory and stakeholder theory in the establishment of the research model. The data collection was executed using a questionnaire; a total of 140 questionnaires returned and 136 usable responses were collected from managers of companies certified with ISO 14001 EMS by SIRIM Malaysia. The data collected were subjected to a partial least square structural equation modeling (PLS-SEM) analysis using the Smart PLS 3.2.7 software version. The results indicated that carbon strategies directly influence the implementation of carbon accounting; carbon accounting directly improves carbon performance, and carbon performance directly enhances organizations‘ financial performance. In addition, carbon accounting is found to exert a full mediation effect on the relationship between carbon strategies and carbon performance. Meanwhile, government carbon initiatives do not exert moderation effect on the relationship between carbon accounting and carbon performance. However, contrary to the prediction, the results failed to validate carbon governance as one of the carbon strategies that influences carbon accounting implementation. The results also showed that carbon accounting failed to exert a full mediation effect on the relationship between carbon governance and carbon performance. As for the control variables effects in the post-hoc analysis, the results showed that only organizations' ownership has the control effects on financial performance. This study has integrated a resource-based theory as the over-arching theory; it explains that a managerial structure determines which strategic resources of a business organization can be utilized to achieve sustainable competitive advantage. Correspondingly, this study found that the sampled companies utilize their business resources by incorporating carbon strategies through carbon accounting to achieve a superior carbon performance. This study validated the predictive role of corporate carbon strategies and carbon accounting‘s mediating role; it also revealed the significant paths leading to a superior firm performance among the SIRIM Malaysia ISO 14001 EMS certified companies. Altogether, the findings of this study provide useful insights for Malaysian companies and the government in becoming carbon neutral organizations, industries, and nations.